2019
DOI: 10.1037/sah0000160
|View full text |Cite
|
Sign up to set email alerts
|

Perceived racial discrimination, anxiety sensitivity, and mental health among Latinos in a federally qualified health center.

Abstract: This investigation examined the explanatory role of anxiety sensitivity in the relationship between perceived racial discrimination and anxiety–depressive symptoms and disorders among Latinos seeking health services at a Federally Qualified Health Center (FQHC). Participants included 202 Spanish-speaking Latino adults (86.1% female; Mage = 38.99 years, SD = 12.43) who completed a structured interview and study measures. Results indicated perceived racial discrimination was indirectly related to depression, soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 54 publications
2
9
0
Order By: Relevance
“…It would therefore be important to replicate the findings in another sample, controlling for trait level of negative affect, to elucidate the unique effects of AS over and above general negative affect. That said, it is important to note here that past work has recurrently demonstrated AS maintains incremental predictive power relative to trait level negative affect across decades of research (Eifert et al 1999;Schmidt et al 2006;Zvolensky et al 2005Zvolensky et al , 2019.…”
Section: Discussionmentioning
confidence: 93%
“…It would therefore be important to replicate the findings in another sample, controlling for trait level of negative affect, to elucidate the unique effects of AS over and above general negative affect. That said, it is important to note here that past work has recurrently demonstrated AS maintains incremental predictive power relative to trait level negative affect across decades of research (Eifert et al 1999;Schmidt et al 2006;Zvolensky et al 2005Zvolensky et al , 2019.…”
Section: Discussionmentioning
confidence: 93%
“…Longitudinal studies have shown that anxiety sensitivity is a significant mediator of the relationship between life stressors and negative affect (McLaughlin & Hatzenbuehler, 2009; Zavos et al, 2012). Furthermore, anxiety sensitivity has been found to function as a mediator between several cultural stressors, including acculturative stress (Bakhshaie et al, 2018; Jardín et al, 2018), ethnic discrimination (Zvolensky et al, 2019), and subjective social status (Zvolensky et al, 2015) and depression among Latinx samples. Again, limited studies have tested whether these findings hold among Latinx women while including their experiences of sexism.…”
Section: Mediation Pathways To Depressionmentioning
confidence: 99%
“…Traditionally, these models have been critical in identifying the potential constructs and vulnerabilities underlying the relationship between cultural stressors and psychological health (Chun, Moos, & Cronkite, 2006; Lazarus & Folkman, 1984). As such, empirical work has highlighted the role of anxiety sensitivity , or one’s heightened awareness and negative interpretation of autonomic arousal (Reiss, Peterson, Gursky, & McNally, 1986), and expressive suppression , or inhibiting expression of emotion (Gross, 1998), as key mechanisms that contribute to negative mental health outcomes (Zvolensky et al, 2019). Still, the relative function of stress responses in changing psychological health is dependent on cultural context and environment (Driscoll & Torres, 2013).…”
mentioning
confidence: 99%
“…All MINI‐KID interviews were videotaped and all diagnoses made were reviewed during supervision sessions with assessors. Fifteen percent of videotaped interviews were reviewed for interrater reliability; as in past work using fully structured interview formats (Duncan et al., 2018; Zvolensky et al., 2019), no instances of diagnostic disagreement were found.…”
Section: Methodsmentioning
confidence: 99%